Nikander, S.: Studies on the Exocrine Ducts of the Pancreas and the Liver in Reindeer (Rangifer tarandus tarandus L.) - Nikander, Sven (Rangifer, 1991)
Sven Nikander defended his D.Med.Vet. thesis "Studies on the Exocrine Ducts of the Pancreas and the Liver in Reindeer (Rangifer tarandus tarandus L.)" at the College of Veterinary Medicine, Helsinki, Finland on 10 June 1991.